223 A three protein signature fails to externally validate as a biomarker to predict surgical outcome in high grade serous ovarian cancer. (13th November 2020) - Hawarden, A; Price, M; Wilson, G; Russell, B; Farrelly, L; Embleton-Thursk, A; Parmar, M; Edmondson, RJ
Abstract : Introduction: Complete cytoreduction is associated with improved survival in patients with advanced High Grade Serous Ovarian Cancer (HGSOC). To aid clinical decision making, many surgical outcome prediction tools have been proposed, but none have been sufficiently validated to warrant routine clinical usage. Here we attempted to externally validate a promising three protein signature, which had shown strong association with suboptimal surgical debulking (AUC 0.89, accuracy 92.8%). Methods: 241 HGSOC tumour samples were collected from patients who participated in a large multicentre trial (ICON5). Samples were collected at the time of initial surgery and before randomisation. Surgical outcome data were collated from the study records. Immunohistochemical scores were generated by two independent observers for the three proteins in the original signature (POSTN, CXCL14 and pSmad2/3). Predictive values were generated for individual and combination protein signatures and as part of a multivariable model using logistic regression. Results: When assessed individually, none of the proteins showed any predictive affinity for suboptimal surgical outcome in our cohort (AUC POSTN 0.55, pSmad 2/3 0.53, CXCL 14 0.62). The combined signature again showed poor predictive ability, AUC 0.58, as did the multivariable model, AUC 0.63. Conclusion: Despite showing original promise, when this protein signature is applied to a large external cohort, it is unable to accurately predictive surgical outcomes. This could be attributed to overfitting of the original model, or differences in surgical practice in our cohort.